Comparison of maloclusion prevalence in Elementary School children with different economic levels (case study in SDN Inpres Kera-Kera and SDIT Al-Biruni Makassar) - Ardiansyah S. Pawinru; Muhammad IA. Bahar (DiscoverSys Inc., 2021)
Objective: To determine the comparison of the prevalence of malocclusion between elementary school children with high economic level and low economic level. Material and Methods: The subjects of this study were students of Kera-Kera Inpres Elementary School and Al-Biruni Makassar SDIT. This type of research is a descriptive observational cross-sectional design by purposive sampling to 103 students. Research subjects will be given a questionnaire and then examined the oral cavity and photographs. Results: In this study subjects, the prevalence of malocclusion was higher in Al-Biruni Makassar SDIT (81.4%) compared to the Kera-Kera Inpres Elementary School (63.6%). Statistical analysis of the Mann-Whitney comparison test values obtained p = 0.072 (p> 0.05). Conclusion: There is no significant difference in prevalence between SD Inpres Kera-Kera and SDIT Al-Biruni Makassar.Conclusion: There is no significant difference in prevalence between Kera-Kera Inpres SD and Al-Biruni Makassar SDIT with a Mann-Whitney comparison test value p = 0.072 (p> 0.05).